Oral Presentations Abstracts: ENDING MALARIA WITH GENE DRIVE TECHNOLOGIES? A NORMATIVE ANALYSIS OF THE ROLE OF HUMANS IN NATURE - DE GRAEFF, Nienke; JONGSMA, Karin; BREDENOORD, Annelien (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Gene drive technologies (GDT) promote the rapid, progressive spread of gene alterations within a population or a species of wild organisms. If GDT are successfully developed and implemented, they could help to resolve intractable problems in the realm of vector-borne disease, invasive species and pest control, but these technologies have also raised concerns regarding the moral permissibility of interfering in nature in this way. In particular, it has been argued that perspectives on humans’ relationship to nature and their impact on and manipulation of ecosystems play a crucial role in determining the moral permissibility of GDT. Nonetheless, these perspectives have thus far remained underexplored in the emerging ethical debate on GDT. In this presentation, I identify these perspectives and concerns and analyse them normatively. Four issues are demonstrated to be of central importance in deciding whether (a particular) use of GDT is in accordance with the relationship humans should have to nature: (1) the moral status of and direct duties towards different organisms; (2) the prioritisation of duties towards different organisms in case of conflicting claims; (3) the moral (ir)relevance of ‘wildness’; and (4) the moral status of holistic entities such as species and ecosystems. The normative positions that can be taken on these issues are presented and critically assessed to determine the moral permissibility of particular applications of GDT. Doing so elucidates the central trade-offs and points of contention in the ethical debate on interfering in nature in this way.